Euphemism In Public Communication (Based On Age And Status) (Conference on English Language Teaching, 2023)
The purpose of this research is to describe the use of euphemistic expressions in public communication based on age and status. The problems that will be explored in this study are: 1) How is the use of euphemisms in communication groups of students and the general public? 2) What are the reasons for euphemisms used by speakers in public communication? 3) What is the role of euphemism in public communication based on age and status? 4) What influences the use of euphemisms in public communication based on age and status so that they can be mutually understood? 5) What are the advantages of euphemism in social life? The method used in this research is the descriptive-qualitative research method. This study found a number of uses of euphemistic expressions in public communication with a total of 17 expressions, there are 9 expressions of the use of euphemisms by groups with student status and 8 expressions of the use of euphemisms by groups of the general public.